The Role of Intercultural Dimension in Developing EFL Students’ Negotiation of Meaning in Salahaddin University-Erbil (Raparin Journal of Humanities (RJH), 2023)
The recognition of the intercultural dimension as a key component in language learning and teaching has been one of the most significant changes in the last few decades. The nature of the experience of teaching and learning languages has significantly changed as a result of this transition. This quantitative study presents the results of an investigation of the role of the intercultural dimension in developing EFL students’ Intercultural Communicative Competence (ICC) and negotiation of meaning at Salahaddin University-Erbil (SUE). The aim of the study is to find out teachers’ and students’ perceptions about the intercultural dimension in language teaching and to discover the role of the intercultural dimension in developing students’ negotiation of meaning. That is to say, to what extent does being aware of other cultures, especially the target culture develop students’ knowledge, skills, awareness and attitude to effectively and meaningfully negotiate? This study attempts to find out whether EFL teachers in SUE integrate culture into classes or not. For the purpose of data collection, a total of 148 EFL students and 30 EFL teachers in the College of Education, College of Languages, and College of Basic Education at Salahaddin University-Erbil were selected as the study participants. Instruments such as teachers’ and students’ questionnaires were used to collect data from the participants. The result of the study revealed students’ and teachers’ positive perceptions towards the intercultural dimension of language teaching. Also, the findings confirmed that the intercultural dimension in language teaching develops students’ knowledge, skills, attitudes, and awareness of students’ own culture and others which are fundamental for students to negotiate meaningfully and effectively with speakers of other cultures. The result also revealed that despite teachers’ positive attitude towards the intercultural dimension in language teaching they do not fully integrate culture into their classes due to the shortage of time and being obliged to follow and finish the curriculum